Healthy City-Based Nutrition Literacy Model for Stunting Management and Improvement of Healthy Living Behavior - Makhrajani Majid; Andi Jusman Tharihk; Rahmat Zarkasy (Jurnal Ilmiah Kesehatan (JIKA), 2022)
The incidence of stunting was mostly found at the age of 12 to 59 months. 90% of human brain growth occurs from the fetus until before the child is five years old. In fact, 70% of brain growth occurs under the age of 2 years. This study aims to determine how the health city-based nutritional literacy model for stunting prevention and improvement of healthy living behavior. This study uses an experimental method in the form of a quasi-experimental one-group pretest-posttest design. The sample was some mothers who have babies in the Work Area of ??the Cempae Public Health Center, Parepare City. Sampling was done by accidental sampling method with as many as 100 people. Data analysis using the Wilcoxon test. The results of this study indicate that there was a change in knowledge after the intervention with the average score being 43,76 with a minimum score of 41 and a maximum value of 45. The attitude of subjects there changed after the intervention, the average score becomes 35,97 with a minimum value of 30 and a minimum score of 30 with, a maximum of 40. It was recommended to increase nutritional literacy regarding stunting prevention and healthy living behavior.